2022
DOI: 10.3390/foods11142154
|View full text |Cite
|
Sign up to set email alerts
|

Carob: A Sustainable Opportunity for Metabolic Health

Abstract: Carob (Ceratonia siliqua L.) is an evergreen tree that belongs to the Leguminosae family and grows in the arid and semi-arid regions of the Mediterranean basin. The carob tree is resistant to droughts and salinity, while its deep root systems allow CO2 to sink, mitigating global warming effects. Traditionally, carob has been used to produce animal feed, but for many years, it was excluded from the human diet. Nowadays, agricultural and industrial sectors exploit carob fruit, also referred to as carob pod, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 114 publications
(181 reference statements)
2
33
0
Order By: Relevance
“…In view of the growing climatic crisis Ceratonia siliqua L. can be a promising course of action both ecologically as well as economically, which contributes to the Sustainable Development Goals across the Mediterranean area: SDG2, to eliminate hunger by promoting sustainable agriculture and the conservation of local biodiversity and improving nutrition; SDG3, to strengthen good health and wellbeing; SDG12, to manage consumption and production using renewable resources, reducing toxic waste, decreasing the C footprint and changing cultivation e.g. wheat to carob; SDG13, to prevent climate change and its impacts by specific actions such as to restore forest land, like carob land, to avoid the increase in agricultural use and industrialization; and SDG15, to promote sustainable forest management, combat desertification, halt and reverse land degradation, and halt biodiversity loss (Gioxari et al, 2022;UNICEF, 2022).…”
Section: Agri-food Chain and Sustainable Economymentioning
confidence: 99%
“…In view of the growing climatic crisis Ceratonia siliqua L. can be a promising course of action both ecologically as well as economically, which contributes to the Sustainable Development Goals across the Mediterranean area: SDG2, to eliminate hunger by promoting sustainable agriculture and the conservation of local biodiversity and improving nutrition; SDG3, to strengthen good health and wellbeing; SDG12, to manage consumption and production using renewable resources, reducing toxic waste, decreasing the C footprint and changing cultivation e.g. wheat to carob; SDG13, to prevent climate change and its impacts by specific actions such as to restore forest land, like carob land, to avoid the increase in agricultural use and industrialization; and SDG15, to promote sustainable forest management, combat desertification, halt and reverse land degradation, and halt biodiversity loss (Gioxari et al, 2022;UNICEF, 2022).…”
Section: Agri-food Chain and Sustainable Economymentioning
confidence: 99%
“…The result of chemical composition for roasted carob powder was in the range of Amer et al (2019), who reported the carob powder contained 5.1 % protein, 0.55 % fat, 3.5 % ash, and 10.99 % fiber. Carob bean gum had the highest significant total carbohydrates contents, this is due to the galactomannan makes up the majority of gum, and after seed processing, crude galactomannan can go through additional steps to remove both protein content and contaminants (Gioxari et al, 2022). El-Kholy et al (2015) analyzed the chemical composition of carob bean gum, and they found that carob bean gum contained 11.17, 0.74, 0.92, 0.73, 0.65, and 96.96% of moisture, crude protein, fat, crude fiber, ash, and total carbohydrates, respectively.…”
Section: Chemical Composition Of Raw Materialsmentioning
confidence: 99%
“…As expected, the cereal bars with carob (SC and SCB) presented a higher content of total phenols (p<0.05). Carob was reported to be rich in phenolic compounds like gallic acid, gallotannins, cinnamic acid, myricetin, and flavonoids (Gioxari et al, 2022). Youssef et al (2013) reported 11 phenolic compounds in the carob powder, among which pyrogallol, catechol, chlorogenic and protocatechuic acids are the most abundant.…”
Section: Antioxidant Activity and Total Phenolic Contentmentioning
confidence: 99%